General Knowledge or The Use of Menstrual Cycle Tracking App among Medical Students at Sriwijaya University - Zafira Alysha; Eka Handayani Oktharina; Liniyanti D. Oswari; Hadrians Kesuma Putra; Rara Inggarsih (Fakultas Kedokteran Universitas Sriwijaya, 2024)
Introduction. As technology and science develop, the menstrual cycle can be known practically by using menstrual cycle tracking applications on gadgets. The many features in the application are an added value, so many women choose to use menstrual cycle tracking applications compared to other platforms. This research aims to identify the general level of knowledge or use of the menstrual cycle tracking app among medical students at the Faculty of Medicine Sriwijaya University. Methods. This type of research is descriptive using a survey. The sample in this study was female medical students at the Faculty of Medicine Sriwijaya University class 2018—2023 who fulfilled the inclusion and exclusion criteria. Sampling was collected by total sampling. Results. In this study, 868 respondents participated, it was found that 467 (53.8%) had the highest level of knowledge, namely with “good” category. 685 (78.9%) controlled their menstrual cycles. 450 (65%) used a menstrual cycle tracking application with the most duration of use being ≥ 1 year 311 (49.8%). The most widely used application name is Flo My Health & Period Tracker 308 (66.5%). 294 (63.9%) chose the quite satisfied category for the level of satisfaction with using the application. In addition, 396 (86.1%) chose the sufficient category for the level of accuracy in using the application. Conclusion. Female medical education students at the Faculty of Medicine, Sriwijaya University have a general level of knowledge with the dominance of the category “good” and a usage rate of 467 (53.8%) in the menstrual cycle monitoring application.